(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
The design and quality of academic environments play a crucial role in shaping students’ learning experiences and engagement. Although eco-conscious academic spaces that incorporate natural elements and sustainable design are gaining global attention, empirical evidence from Nepalese higher education remains limited. This study examines undergraduate students’ perceptions of eco-friendly academic spaces and assesses the ecological and psychological support provided by existing campus environments. Grounded in Person–Environment Fit Theory, the study adopts a quantitative, positivist approach using a structured questionnaire administered to students from institutions in the Chitwan and Nawalparasi districts. Data were analyzed using Principal Component Analysis and binary logistic regression. Findings reveal that students generally perceive their campuses as lacking eco-friendly and psychologically supportive features. This study indicates tha students who associate natural environments with well-being are more likely to prefer green academic spaces, whereas emotional attachment to nature was not a significant predictor. The study proposes MECAS (Mindful Eco-Conscious Academic Space) and offers practical implications for sustainable, student-centered campus design.